Pengaruh Penggunaan Gadget bagi Keluarga di Paroki Santo Antonius Padua Taratara - Paulus Joseph Mentang; Fransiska Karamoy (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
Technological progress (Gadgets) aims to make all human activities easier, but this must also be accompanied by a wise attitude of humans as users of this technology. Gadgets function to facilitate virtual interaction and communication, but if used unwisely they have the potential to be bad for communication and interaction between users. This article carries the title